The vasoactive potential of kisspeptin-10 in the peripheral vasculature. - Iain Sawyer; Sarah-Jane Smillie; Jennifer V Bodkin; Elizabeth Fernandes; Kevin T O'Byrne; Susan D Brain (PLoS ONE, 2011)
Splice products of the Kiss1 protein (kisspeptins) have been shown to be involved in a diverse range of functions, including puberty, metastasis and vasoconstriction in large human arteries. Circulating Kisspeptin-10 (Kp-10) plasma levels are low in normal individuals but are elevated during various disease states as well as pregnancy. Here, we investigated the potential of Kp-10, the shortest biologically active kisspeptin, to influence microvascular effects, concentrating on the cutaneous vasculature. Kp-10 caused a dose-dependent increase in oedema formation (0.3-10 nmol/injection site), assessed by Evans Blue albumin dye extravasation, in the dorsal skin of CD1 mice. Oedema formation was shown to be inhibited by the histamine H(1) receptor antagonist mepyramine. The response was characterised by a ring of pallor at the injection site in keeping with vasoconstrictor activity. Therefore, changes in dorsal skin blood flow were assessed by clearance of intradermally injected (99m)technetium. Kp-10 was found to significantly reduce clearance, in keeping with decreased blood flow and providing further evidence for vasoconstrictor activity. The decreased clearance was partially inhibited by co-treatment with the cyclo-oxygenase inhibitor indomethacin. Finally evidence for the kisspeptin receptor gene (Kiss1R), but not the kisspeptin peptide gene (Kiss1), mRNA expression was observed in heart, aorta and kidney samples from normal and angiotensin II induced hypertensive mice, with similar mRNA levels observed in each. We have evidence for two peripheral vasoactive roles for kisspeptin-10. Firstly, plasma extravasation indicative of ability to induce oedema formation and secondly decreased peripheral blood flow, indicating microvascular constriction. Thus Kp-10 has vasoactive properties in the peripheral microvasculature.